2017
DOI: 10.1186/s13047-017-0192-7
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography derived bone density measurement in the diabetic foot

Abstract: BackgroundThe accurate and reliable measurement of foot bone density is challenging and there is currently no gold standard technique. Such measurement is particularly valuable in populations at risk of foot bone pathology such as in those with long term diabetes. With research and development, computed tomography may prove to be a useful tool for this assessment. The aim of this study was to establish the reliability of a novel method of foot bone density measurement in people with diabetes using computed tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
3
4
0
1
Order By: Relevance
“…A comparison of our findings to pre-existing reference values is therefore not possible at this point. Nonetheless, a recent investigation by Barwick et al [22] on derived bone densities in the diabetic foot presented average HU values of the calcaneus which are comparable to our findings, despite the underlying disease in the patient population.…”
Section: Discussionsupporting
confidence: 90%
“…A comparison of our findings to pre-existing reference values is therefore not possible at this point. Nonetheless, a recent investigation by Barwick et al [22] on derived bone densities in the diabetic foot presented average HU values of the calcaneus which are comparable to our findings, despite the underlying disease in the patient population.…”
Section: Discussionsupporting
confidence: 90%
“…There are several existing studies that use clinical CT to evaluate BMD in the midfoot 23 . A clinical CT study in the medial cuneiform showed the highest density in the distal‐dorsal‐lateral site with increasing density in the dorsal and distal directions, 17 matching the density trends seen in our study.…”
Section: Discussionsupporting
confidence: 86%
“…Five regions of interest (ROIs) for the five different mineral contents of the reference phantom (Mindways Inc., Austin, TX, USA) were recorded in the same CT images. For the CT image of each patient, the phantom-based calibration algorithm [28, 29] determined the linear correlation between the known mineral densities and their corresponding HU values as follows:BMDphantom=α×HU+β,where α and β are the patient-specific values that are to be determined. Thus, using equation (1) with the determined α and β , the voxelwise BMD values of the lumbar spine and hip of each patient were calculated as the ground truth.…”
Section: Methodsmentioning
confidence: 99%